REKONSTRUKSI KONSEP QIWAMAH (KEPALA KELUARGA) DALAM Q.S. AL-NISA’ AYAT 34 PERSPERKTIF MAQASID SYARI’AH AL SYATHIBI - Amrin Borotan; Adi Harmanto (Jurnal Syaikh Mudo Madlawan: Kajian Ilmu-Ilmu Keislaman, 2025)
Indonesian religious scholars and marriage regulations outline that the role of qiwamah or leadership in the family should and should only be in the hands of men. However, in the reality of some Indonesian family life, the rule does not work as it should, in das sollen. Because in fact, in das sein, found not a few women who became heads or leaders in their families. This view is based on the scholars' understanding of the interpretation of the concept of qiwamah stated in Q.S al Nisa' verse 34. This article aims to reinterpret the concept of the head of household or qiwamah written in Q.S al Nisa' which is gender-responsive using the theory  of maqashid shari'ah al Shatibi. The results showed that based on the review of the maqasid  shari'ah of Shatibi, who occupies the purpose of dharuriyyat that must exist in the concept of qiwamah is the fulfillment of income and the availability of parties who are able to lead in the household. Then those who occupy Hajyyat in qiwamah are those who carry out the fulfillment of the necessities of life and are leaders in the household between husband and wife. While occupying tahsiniyyat is about the form of leadership that will be carried out, it can be based on male leadership female leadership, or collective leadership, namely the division of leadership between the two.